Toxicity and Efficacy of Stereotactic Ablative Body Radiotherapy for Moderately Central Non-small Cell Lung Cancers Using 50 Gy in Five Fractions. Issue 4 (April 2020) - Rulach, R.; McLoone, P.; Lumsden, G.; McKay, S.; MacLaren, V.; Macphee, J.; Moore, K.; Omand, M.; Sproule, M.; Currie, S.; Aitken, A.; Ferguson, R.; et al.
Abstract: Aims: Stereotactic ablative body radiotherapy doses for peripheral lung lesions caused high toxicity when used for central non-small cell lung cancer (NSCLC). To determine a safe stereotactic ablative body radiotherapy dose for central tumours, the phase I/II Radiation Therapy Oncology Group RTOG 0813 trial used 50 Gy/five fractions as a baseline. From 2013, 50 Gy/five fractions was adopted at the Beatson West of Scotland Cancer Centre for inoperable early stage central NSCLC. We report our prospectively collected toxicity and efficacy data. Materials and methods: Patient and treatment characteristics were obtained from electronic medical records. Tumours were classed as moderately central or ultra-central tumours using published definitions. Toxicity was assessed in a centralised follow-up clinic at 2 weeks, 6 weeks, 3 months, 6 months, 1 year and 2 years after treatment. Results: Fifty patients (31 women, 19 men, median age 75.1 years) were identified with T1-2N0M0 moderately central NSCLC; one patient had both an ultra-central and a moderately central tumour. Eighty-four per cent were medically unfit for surgery. Forty per cent had biopsy-proven NSCLC and 60% were diagnosed radiologically using 18-fluorodeoxyglucose positron emission tomography/computed tomography imaging. Fifty-six per cent of patients were Eastern Cooperative Oncology Group (ECOG) performance status 2 or worse. All patients received 50 Gy/five fractions on alternate days on schedule. Two patients died within 90 days of treatment, one from a chest infection, the other cause of death was unknown. There was one episode of early grade 3 oesophagitis and one grade 3 late dyspnoea. There was no grade 4 toxicity. Over a median follow-up of 25.2 months (range 1–70 months), there were 34 deaths: 18 unrelated to cancer and 16 due to cancer recurrence. The median overall survival was 27.0 months (95% confidence interval 20.6–35.9) and cancer-specific survival was 39.8 months (95% confidence interval 28.6, not reached). Conclusion: This study has shown that 50 Gy/five fractions is a safe dose and fractionation for early stage inoperable moderately central NSCLC, with outcomes comparable with other series, even with patients with a poor performance status. Highlights: Stereotactic radiotherapy for central lung cancer is associated with high toxicity. 50 patients with central lung cancers were treated with 50 Gy in 5 fractions. The overall grade 3 toxicity rate was 4% with 2 deaths within 90 days of treatment. Median overall and cancer-specific survival was 27 and 39.8 months, respectively. 50 Gy in 5 fractions is an acceptable treatment for moderately central lung cancer.